Pruritus Is Associated with an Increased Risk for the Diagnosis of Autoimmune Skin Blistering Diseases: A Propensity-Matched Global Study - Ulrike Raap; Maren M. Limberg; Khalaf Kridin; Ralf J. Ludwig (Biomolecules, 2023)
Autoimmune bullous skin diseases (AIBDs), such as bullous pemphigoid (BP) and pemphigus, are characterized and caused by autoantibodies targeting structural proteins. In BP, clinical experience and recent systematic evaluation identified pruritus to be common and an important cause of impaired quality of life. Furthermore, chronic pruritus may be the sole clinical symptom of BP. In pemphigus, a retrospective study recently documented a high prevalence of pruritus. The temporal relation between pruritus and BP/pemphigus are, however, unknown. Likewise, the presence of pruritus in AIBDs other than BP and pemphigus is unknown. To address this, we performed propensity-matched retrospective cohort studies using TriNetX, providing real-world patient data to (i) assess the risk to develop AIBDs following the diagnosis of pruritus and (ii) vice versa. We assessed this in eight AIBDs: BP, mucous membrane pemphigoid (MMP), epidermolysis bullosa acquisita, dermatitis herpetiformis, lichen planus pemphigoides (LPP), pemphigus vulgaris, pemphigus foliaceous, and paraneoplastic pemphigus (PNP). For all AIBDs, pruritus was associated with an increased risk for the subsequent diagnosis of each of the eight investigated AIBDs in 1,717,744 cases (pruritus) compared with 1,717,744 controls. The observed hazard ratios ranged from 4.2 (CI 3.2–5.5; p < 0.0001) in MMP to 28.7 (CI 3.9–211.3; p < 0.0001) in LPP. Results were confirmed in two subgroup analyses. When restricting the observation time to 6 months after pruritus onset, most HRs noticeably increased, e.g., from 6.9 (CI 6.2–7.9; p < 0.0001) to 23.3 (CI 17.0–31.8; p < 0.0001) in BP. Moreover, pruritus frequently developed following the diagnosis of any of the eight AIBDs, except for PNP. Thus, all AIBDs should be considered as differential diagnosis in patients with chronic pruritus.